Strategic management and business policy - Wheelen, Thomas L (Pearson, 2015)
Includes bibliographical references and index; Basic concepts in strategic management -- Corporate governance -- Ethics and social responsibility in strategic management -- Scanning the environment -- Environmental scanning & industry analysis -- Internal scanning & organizational analysis -- Strategy formulation -- Strategy formulation : situation analysis & business strategy -- Strategy formulation: corporate strategy -- Strategy formulation: functional strategy & strategic choice -- Strategy implementation and control -- Strategy implementation: organizing for action -- Strategy implementation: staffing & directing -- Evaluation & control -- Introduction to case analysis -- Suggestions for case analysis